THE EFFECT OF Trichoderma harzianum ON DELIVERY SYSTEMS IN ENHANCING SEEDS GERMINATION AND SEEDLINGS GROWTH OF SOUR ORANGE (Citrus urantium) - Falih H. Saeed (Mesopotamia Journal of Agriculture)
This study was conducted to evaluate the effect of the delivery systems (Soil treatment , seeds tretment , with water irrigation) of three Trichoderma harzianum isolates (T.9 ,T.26 and T.28) in enhancing sour orange seeds germination and seedlings growth , The results reverted that vitalization of Trichoderma isolates with water irrigation and as seeds tretment was more efficient than soil treatment , in reducing the period required for seeds germination 21.3 ,21.8 days compared with 24.1days in soil treatment method in increasing percentage of seeds germination 69.01,67.76,65.14% compared to 43.7% in control untreated treatment, The results also showed the suporility of seeds treatment method over soil treatment and irrigation treatment in enhancing seedling growth 16.47cm,14.3cm,0.62gm, 1.7gm,0.22gm and 0.59gm for tested plant growth parameters stem length , root length ,fresh weight of root system, fresh weight of shoot system , dry weight of root system and dry weight of shoot system respectively.